2012
DOI: 10.1177/1721727x1201000103
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Ethyl Pyruvate on Tumor Growth and Metastasis in a Severe Combined Immunodeficiency Mouse Orthotopic Implantation Model

Abstract: Ethyl pyruvate (EP) has been shown to have significant anti-inflammatory activities. Here, we explore the therapeutic effects of EP administration on tumor growth and metastasis in orthotopic implantation human gastric cancer models in severe combined immunodeficiency (SCID) mice. After SCID mice were treated with EP, the tumor growth and liver metastasis from gastric cancer were investigated and its possible molecular mechanisms were further studied. As a result, it was found that EP could inhibit tumor growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…HMGB1 interferes with the apoptotic machinery at the level ofcaspase-9 activation and inhibits cell apoptosis via c-IAP2 induction in the pathogenesis of colon carcinoma (28), while RAGE limits apoptosis through a p53dependent mitochondrial pathway in tumor cell (29). Previous studies have shown that blockade of HMGBl-RAGE axis by EP inhibits the growth and metastasis of malignant tumors via negative regulation ofPCNA, MMP-9 and positive regulation of p53 (24,30). Our present study showed that EP suppressed GBC growth and invasion via negative regulation ofPCNA, MMP-9 and positive regulation ofp53, which might be mediated byHMGBl-RAGE axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HMGB1 interferes with the apoptotic machinery at the level ofcaspase-9 activation and inhibits cell apoptosis via c-IAP2 induction in the pathogenesis of colon carcinoma (28), while RAGE limits apoptosis through a p53dependent mitochondrial pathway in tumor cell (29). Previous studies have shown that blockade of HMGBl-RAGE axis by EP inhibits the growth and metastasis of malignant tumors via negative regulation ofPCNA, MMP-9 and positive regulation of p53 (24,30). Our present study showed that EP suppressed GBC growth and invasion via negative regulation ofPCNA, MMP-9 and positive regulation ofp53, which might be mediated byHMGBl-RAGE axis.…”
Section: Discussionmentioning
confidence: 99%
“…But, targeting HMGBI by EP inhibits hepatic tumor growth (22) and exerts antitumor activity via inhibition of indoleamine 2, 3-dioxygenaseour (23). In addition, based on our previous research, EPmediated inhibition of HMGBI-RAGE axis could suppress growth and invasion of gastric cancer cells and severe combined immunodeficiency mouse orthotopic implantation model (24). Thus, EP may have the potential as a new multi-functional drug candidate for cancer therapy and be widely used in clinical settings to treat malignant tumMoreover, in the present study, the possible molecular mechanism of EP on GBC cell growth and invasion need be comprehensively explored.…”
Section: Fig 4 Effects Ofep Administration On Gbc Cell Invasion A)mentioning
confidence: 99%
“…Exercise has been shown to enhance in vitro macrophage antitumor cytotoxicity (60)(61)(62)(63)(64) and, in accordance with the immune surveillance theory, it is to be expected that moderate exercise protects against malignancy whereas exhaustive exercise is linked to increased cancer risk. Relatively low intake of fruit and vegetables is a risk factor for many of the most important chronic diseases (65)(66)(67)(68)(69)(70), whereas greater consumption of natural products -including, spices, nuts, whole-grain cereals, legumes, fruits and vegetables is associated with a lower risk of many diseases (71)(72)(73)(74)(75)(76). Chronic inflammation is one of the foremost risk factors for different types of cancer.…”
mentioning
confidence: 99%
“…It has been reported that mast cells express leptin and leptin receptors, a finding implicating paracrine or autocrine immunomodulatory effects of leptin on mast cells (32)(33)(34)(35). Leptin may playa role in ASD.…”
mentioning
confidence: 99%